2021
DOI: 10.3390/ph14111183
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Terminalia catappa L. Extract on the Migration and Invasion of Human Glioblastoma Multiforme Cells

Abstract: Glioblastoma multiforme (GBM) is one of the most aggressive and common types of brain tumor. Due to its high proliferation ability, a high lethality rate has been observed with this malignant glial tumor. Terminalia catappa L. (T. catappa) is currently known to have anti-inflammatory and anti-carcinogenesis effects. However, few studies have examined the mechanisms of the leaf extracts of T. catappa (TCE) on GBM cells. In the current study, we demonstrated that TCE can significantly inhibit the migration and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Matrix metalloproteinases, a family of zinc-dependent proteinase, have long been associated with tumor cell invasion and metastasis for its ability in activating cancer cells, modulating immune function, degrading extracellular matrix and basement membrane. [25][26][27][28] In particular, matrix metalloproteinase-9 (MMP-9) has been widely investigated to relate to the pathology of cancer. [29][30][31] TPA (12-O-Tetradecanoylphorbol-13-acetate), a phorbol ester, has been well-documented on cancer metastasis in several cancer types.…”
mentioning
confidence: 99%
“…Matrix metalloproteinases, a family of zinc-dependent proteinase, have long been associated with tumor cell invasion and metastasis for its ability in activating cancer cells, modulating immune function, degrading extracellular matrix and basement membrane. [25][26][27][28] In particular, matrix metalloproteinase-9 (MMP-9) has been widely investigated to relate to the pathology of cancer. [29][30][31] TPA (12-O-Tetradecanoylphorbol-13-acetate), a phorbol ester, has been well-documented on cancer metastasis in several cancer types.…”
mentioning
confidence: 99%
“…In the past, our laboratory has also studied TCE in other cancer metastases ( Chu et al, 2007 ; Yang et al, 2010 ; Yeh et al, 2012 ; Chung et al, 2021 ). We demonstrated that TCE negatively affected metastasis in various cancers, including hepatocellular carcinoma, oral cancer, human glioblastoma, and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the medicinal potentials of this species, the majority of studies have focused on physiochemical and biological characteristics of the leaf. T. catappa leaf have been shown for its high potential in treatment diabetes using aqueous extract (11,12), protection of human skin fibroblasts from oxidative stress using methanol extract (13), inhibition of metastasis of oral, lung and brain cancer (14)(15)(16). Both aqueous extract and ethanol of T. catappa leaf exhibited antioxidant activity, probably due to significant amount of polyphenolic and flavonoid contents (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%